Select the right flat-panel technology. IN HDTV Buying Guide. - Poor, Alfred (PC World Philippines)
Before you drop hundreds or thousands of dollars on the wrong flat-panel HDTV set, read our comprehensive breakdown of everything you need to know. Our HDTV buying guide might just help you save some money.